(untitled) (Gestão & Regionalidade, 2015)
The consumption of plus size clothing for women was investigated with a non-probabilistic sample of 231 consumers. The literature review and the exploratory study enabled identifying antecedents of satisfaction: the expectations and experiences with the aspects of the product and the store and the psychological aspects. Results indicate that the experience with the brand and the store, as well as the psychological aspects, influence in satisfaction. It was also found that younger women with higher education and greater income who wore smaller sizes tend not only to have more expectations but also to demand more to be satisfied.